Study of the effect of institutional ownership on accounting quality and cost of capital - Fallah, Reza (2021)
This study was conducted to investigate the effect of institutional ownership on accounting quality and cost of capital. This research is quasi-experimental in the field of positive accounting research and based on real information in the financial statements of companies. It is also of correlational type and, it is a descriptive (comparative / analytical) research in terms of data collection method. The research methodology is post-event due to the use of historical information in terms of time, and because it can be used in the process of using information and can be used in practice, it is a kind of applied research. The statistical population of the present study includes all companies listed on the Tehran Stock Exchange, with the exception of banks and financial and credit institutions, investment companies, financial intermediaries, holding companies and leasing companies (which have different financial structure and management principles than other companies). The information of these companies for the 7-year period from 2011 to 2017 has been studied. In order to examine the relationship between institutional ownership and quality of accounting information and cost of capital debt and to examine the moderating role of institutional ownership in the relationship between quality of accounting information and cost of capital debt, regression analysis was presented. Also, in the regression analysis, the generalized regression model was fit, and the coefficients of regression variables were estimated. In addition, the test of zero regression coefficients for the significance of the model and each of the variables was performed. The test results of the research hypotheses showed that there is a significant relationship between institutional ownership and quality of accounting information and cost of capital debt, but institutional ownership has not been able to moderate the relationship between quality of accounting information and cost of capital debt.